CO2-Activation by size-selected tantalum cluster cations (Ta1–16+): thermalization governing reaction selectivity. Issue 4 (14th January 2022) - Levin, Nikita; Margraf, Johannes T.; Lengyel, Jozef; Reuter, Karsten; Tschurl, Martin; Heiz, Ulrich
Abstract : Tantalum cluster cations react with CO2 either via transfer of oxygen atoms to the clusters or the adsorption of an entire molecule. The released energy and vibrational heat capacities are assigned to determine the branching ratios of the pathways. Abstract : The reactions of tantalum cluster cations of different sizes toward carbon dioxide are studied in an ion trap under multi-collisional conditions. For all sizes studied, consecutive reactions with several CO2 molecules are observed. This reveals two different pathways, namely oxide formation and the pickup of an entire molecule. Supported by calculations of the thermochemistry of Ta n O + formation upon reaction with CO2, changes in the branching ratios at a particular cluster size are related to heat effects due to the vibrational heat capacity of the clusters and the exothermicity of the reaction.